2007 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--1759
|View full text |Cite
|
Sign up to set email alerts
|

University Of Arkansas Science Partnership Program

Abstract: Dr. Clausen currently serves as Adam Professor of Chemical Engineering at the University of Arkansas. His research interests include bioprocess engineering (fermentations, kinetics, reactor design, bioseparations, process scale-up and design), gas phase fermentations, and the production of energy and chemicals from biomass and waste. Dr. Clausen is a registered professional engineer in the state of Arkansas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…12 Participating schools and teachers committed to full participation in the three-year program. 13,14 Follow-up activities during the academic year, including observations by UA mentors and participating science teachers, were designed to provide additional time for inquiry, reflection, and mentoring and to sustain the long-term practice of including hands-on laboratory activities aligned with the Science Frameworks.…”
Section: Year One Summer Institutementioning
confidence: 99%
See 2 more Smart Citations
“…12 Participating schools and teachers committed to full participation in the three-year program. 13,14 Follow-up activities during the academic year, including observations by UA mentors and participating science teachers, were designed to provide additional time for inquiry, reflection, and mentoring and to sustain the long-term practice of including hands-on laboratory activities aligned with the Science Frameworks.…”
Section: Year One Summer Institutementioning
confidence: 99%
“…For each activity, the Institute provided: 1) a presentation and discussion of the topic background; 2) time to perform the experiment by teachers working in teams; 3) discussion of the experiment, including possible alterations and the problems and/or limitations for use in their classrooms; 4) discussion on how the experiment fits into the state mandated science frameworks; 5) an activity and Institute evaluation; 6) supplies provided to carry out the laboratory activities; 7) a notebook and memory stick containing background material and suggestions for each experiment, a detailed equipment list, a list of experimental procedures and any safety issues to be addressed. Davis, Gattis and Clausen (2007) 13,14 provide a more detailed description of the year one Summer Institute and follow-up activities.…”
Section: Year One Workhop Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers were divided into groups of four to five members from different schools and grade levels and asked to perform the experiments with the assistance of UA faculty. Further details of the Year 1 institute and follow-up activities were presented by Davis et al 5,6 Preparing a mold terrarium 6…”
Section: The Year 1 (2006) Institutementioning
confidence: 99%
“…These evaluations were given daily during each summer institute, and consistently showed that the teachers were very impressed with the content of each of the summer institutes, the knowledge and help of the moderators, and the hands-on experiments that they were able to take back to their classrooms. Details of Year 1 and Year 2 institute evaluations were presented by Davis et al 6,9 Perhaps a better measure of the success of the program is the use of the institute activities in the classroom. As is noted in Table 8, 9 shows a summary of the 2007-2008 and 2008-2009 use of the design activities by the teachers, as reported on surveys collected throughout the school year.…”
Section: Evaluation/use Of Institute Activitiesmentioning
confidence: 99%